2010
DOI: 10.1590/s0102-695x2010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial activity evaluation and MIC determination of liophilizated hydroalcoholic extracts of Bixa orellana L., Bixaceae

Abstract: RESUMO: "Avaliação da atividade antimicobacteriana e a determinação da CIM de extratos hidroalcoólicos liofilizados de Bixa orellana L., Bixaceae." Bixa orellana é usada na medicina popular em várias doenças. Extratos do fruto, raiz e folhas apresentaram atividade antimicrobiana, enquanto extratos do caule mostraram resultados negativos. Este estudo teve por objetivo verificar a atividade antimicobacteriana de extratos hidroalcoólicos liofilizados de B. orellana frente Mycobacterium tuberculosis e determinar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Although B. orellana is widely used to treat respiratory infections, this is the first report of its kind. The study results are consistent with a previous study reporting MIC values of 0.3, 0.5, and 0.2 mg/mL for B. orellana leaf, seed, and root extracts against M. tuberculosis [ 31 ]. Only few studies have described the antimycobacterial activity of plant-derived products against M. abscessus, for example, the effects of chloroform and ethanolic extracts from seeds of Persea americana (where the activity of the extracts was associated with lignans) [ 32 ], Valencia orange terpeneless oil [ 33 ], and Pelargonium reniforme and P. sidoides root extracts (containing linear chain fatty acids such as palmitic, oleic, and linoleic) [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although B. orellana is widely used to treat respiratory infections, this is the first report of its kind. The study results are consistent with a previous study reporting MIC values of 0.3, 0.5, and 0.2 mg/mL for B. orellana leaf, seed, and root extracts against M. tuberculosis [ 31 ]. Only few studies have described the antimycobacterial activity of plant-derived products against M. abscessus, for example, the effects of chloroform and ethanolic extracts from seeds of Persea americana (where the activity of the extracts was associated with lignans) [ 32 ], Valencia orange terpeneless oil [ 33 ], and Pelargonium reniforme and P. sidoides root extracts (containing linear chain fatty acids such as palmitic, oleic, and linoleic) [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Giridhar and Venugopalan (2012) have observed antibacterial activity of annatto leaves only, corroborating the data reported by Coelho et al (2003) and Fleischer et al (2003). Silva et al (2010), after testing the inhibitory activity against bacteria of B. orellana L. hydroethanolic extracts obtained from the fruit, stem, root and leaves of the plant, found that the products from the leaves and stems exhibited bacteriostatic activity against several bacteria. However, Majolo et al (2013) and Mital et al (2013) used seeds from multiple accessions and concluded that the hydroethanolic preparation exhibited the best inhibitory activity, with Gram-positive bacteria being the most sensitive, resulting in a moderate zone of inhibition.…”
Section: Determination Of the Minimum Inhibitory Concentration And MIsupporting
confidence: 80%
“…Regarding the determinations of antimicrobial activity, variations may exist due to the half-life of the active compounds (photosensitive, thermo-labile, etc. ), the use of different strains of microorganism (phenotype) and the quantification method used (Silva et al, 2010).…”
Section: Mic Of Eebsmentioning
confidence: 99%